Sexual Minority Vulnerability and Fear of Victimization - Doude, Sara (Victims & offenders, 2023)
After emerging as an issue of concern nationally in the last half-century, fear of crime has remained a prominent issue among Americans. Researchers have since begun to explore some of the more complex factors driving fear of crime, both individually and structurally. “Shadow hypotheses” research explores how other, more specific fears may overshadow generalized fear. One area where research is only beginning to address is the fear of crime among sexual minorities. This study aims to examine how fear of crime among sexual minorities is distinguished from fear experienced by heterosexuals. We utilize a series of nested, ordinary least squares regression models to assess the validity of “shadow hypotheses” among sexual minorities and heterosexuals separately. While findings do not lend strong support to the shadow effect of fear for sexual minorities, the research reveals important nuances of fear for both groups. Additionally, it highlights how critical this type of research is to further our understanding of how people experience fear. The research is timely and relevant researchers have recently established that sexual minorities are disproportionately targeted in bullying and hate assaults.